Food Advertisement and Dietary Choices in Adolescents: An Overview of Recent Studies - Anastasia Tsochantaridou; Theodoros N. Sergentanis; Maria G. Grammatikopoulou; Kyriakoula Merakou; Tonia Vassilakou; Eleni Kornarou (MDPI AG, 2023)
Adolescents are exposed to food marketing through many routes, including television, movies, videos, print media, online games, and social media. The interplay between exposure to unhealthy food advertisements and food choices by adolescents is a field of special interest given the ongoing evolution of social media trends and marketing strategies. The purpose of this review was to synthesize the scientific findings in the last five years (2017-2022) regarding the possible influence of nutrition-related advertisements through television, social media, or video games on the choice and consumption of unhealthy foods and drinks in adolescents. Nineteen studies were included in this review. Adolescents exposed to unhealthy food and beverage advertising showed high desire and intention to consume the advertised foods, as evidenced by the majority of included studies. The effects of advertisements are reinforced by peer pressure and influencers and interact with socioeconomic, biological, and environmental factors. Food marketing represents part of the obesogenic environment of the present time.